2014
DOI: 10.3109/14397595.2013.875640
|View full text |Cite
|
Sign up to set email alerts
|

A case of scleredema adultorum successfully treated with narrow-band ultraviolet B phototherapy

Abstract: Scleredema adultorum, also known as scleredema of Buschke, is a rare connective tissue disease with unknown etiology, which is characterized by diffuse skin induration of face, neck, upper chest, back, shoulders and arms. Although there is no established treatment for this disease, the efficacy of phototherapy has been reported. We herein describe a case of scleredema adultorum successfully treated with narrow-band ultraviolet B and discuss a potential mechanism explaining its efficacy for fibrotic skin diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
6
0
1
Order By: Relevance
“…Rodnan skin score, and ultrasonography images taken prior and after treatment This research also further highlights narrow-band UVB phototherapy is as effective as low-dose UVA1 with a significantly lower cost. A case report from Japan highlights similar effectiveness of NB-UVB for scleroderma [10]. A Brazilian retrospective investigation of 11 patients with localized scleroderma found that several kinds of phototherapy, including UVA, PUVA, and NB-UVB, had comparable effectiveness both in terms of clinical and ultrasound evaluation [11].…”
Section: Discussionmentioning
confidence: 99%
“…Rodnan skin score, and ultrasonography images taken prior and after treatment This research also further highlights narrow-band UVB phototherapy is as effective as low-dose UVA1 with a significantly lower cost. A case report from Japan highlights similar effectiveness of NB-UVB for scleroderma [10]. A Brazilian retrospective investigation of 11 patients with localized scleroderma found that several kinds of phototherapy, including UVA, PUVA, and NB-UVB, had comparable effectiveness both in terms of clinical and ultrasound evaluation [11].…”
Section: Discussionmentioning
confidence: 99%
“… If methotrexate fails or is contraindicated, based on a risk‐benefit approach, the following alternative treatments can be proposed: glucocorticoids (systemic or intralesional), cyclosporine, prostaglandin E1, intravenous immunoglobulin, high‐dose penicillin, factor XIII infusion, cyclophosphamide, narrow‐band UVB, radiotherapy, electron‐beam radiotherapy and extracorporeal photopheresis …”
Section: Scleredemamentioning
confidence: 99%
“…Two patients were treated successfully with UVB radiation. Another patient did not respond to UVB treatment but showed a marked improvement after psoralen and ultraviolet A (PUVA)bath therapy (33,39,40). The best results were seen after PUVA therapy, with 3 patients showing marked improvement in symptoms (24,33).…”
Section: Phototherapy (Puva Puva-bath Uvb Uva1)mentioning
confidence: 99%